The Effect of Combination of Calcium Supplement and Physical Exercise on Increasing Muscle Strength in Chronic Ischemic Stroke - Nurjannah; Audry Devisanty Wuysang; Andi Aryandy; Ashari Bahar; Cahyono Kaelan; Aryadi Arsyad (Babali Nursing Research, 2023)
Background: Stroke causes muscle weakness which results in limitations in daily activities such as self-care, eating, walking, etc. Objective: This study aims to evaluate the effect of calcium supplement and physical exercise on increasing muscle strength in chronic ischemic stroke patients. Method: This research used a quasi-experimental pretest-posttest with control group design. This research was conducted at Dadi Makassar Hospital and Haji Hospital from March to May 2023. The sample obtained was 37 subjects based purposive sampling with an unpaired numerical comparative formula for two sample groups. Consisting of 18 people in the treatment group who were given calcium supplements at a dose of 500 mg per day and physical exercise (Both training, Proprioceptive Neuromuscular Facilitation (PNF) and strengthening) and 19 people in the control group who were only given physical exercise. The research was carried out for 6 weeks using a Manual Muscle Testing (MMT) measuring instrument for muscle strength. This research used the Wilcoxon and Mann Whitney test. (α<0.05) Results: There is a significant of increasing lower extremity muscle strength between pretest and posttest in treatment group and control group (p=0.001; p=0.014, p<0.05), There is an increasing of the upper extremity muscle strength between pretest and posttest in treatment group and control group (p=0.001; p=0.025). There is no significant difference of increasing muscle strength in the upper and lower limb between two groups (p=0.051). Conclusion: Calcium supplements and physical exercise were no more significant in increasing muscle strength than physical exercise only in chronic ischemic stroke patients.